2019
DOI: 10.1039/c8ra09465a
|View full text |Cite
|
Sign up to set email alerts
|

Computational investigations into the structural and electronic properties of CdnTen (n = 1–17) quantum dots

Abstract: It is a systematic study on CdnTen quantum dots based on localized (Gaussian) wave functions that discuss the lowest energy geometries and electronic properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Several simulation techniques, ranging from the adiabatic ground state to non-adiabatic excited-state calculations, have been applied to understand the photo-chemo-physical properties of QDs in detail. 25–28 However, most of these attempts 29–37 have focused on stoichiometric QDs (with an equal number of cation and anion atoms) that are less frequently obtained from the conventional synthesis. The more common non-stoichiometric QDs, with cation-to-anion ratios deviating from one, that are critical to many optical and photocatalytic applications, remain largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Several simulation techniques, ranging from the adiabatic ground state to non-adiabatic excited-state calculations, have been applied to understand the photo-chemo-physical properties of QDs in detail. 25–28 However, most of these attempts 29–37 have focused on stoichiometric QDs (with an equal number of cation and anion atoms) that are less frequently obtained from the conventional synthesis. The more common non-stoichiometric QDs, with cation-to-anion ratios deviating from one, that are critical to many optical and photocatalytic applications, remain largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study performed an extensive structural search for CdTe clusters using PSO algorithms as implemented in CALYPSO, evaluated the candidate clusters by DFT and MP2 theory levels. We re-used the lowest energy CdTe structures from our previous work for the sake of the present work (Imran et al, 2019). All the symmetric structures of bare and capped QDs were optimized without symmetry constraints.…”
Section: Methodsmentioning
confidence: 99%
“…In one of our previous studies, we had performed an extensive search for the lowest energy geometries of Cd n Te n QDs (n 1-17) using particle swarm optimization (PSO) algorithms and density functional theory (DFT) approaches and explored structural and electronic properties (Imran et al, 2019). The present study presents structural and electronic properties of bare and capped small-sized Cd n Te n (n 6,8 and 9) QDs.…”
Section: Introductionmentioning
confidence: 99%
“…28 The geometry of a CdTe (1.2 nm diameter) cluster was optimized using the semiempirical PM6 function. Previous computational [29][30][31][32] and experimental 33,34 studies have shown that thiol-type ligands preferentially bind to surface Cd atoms. We performed the calculations using the ligand that produced the highest relative QY for the QDs (thioglycolic acid, TGA).…”
Section: Computational Calculationsmentioning
confidence: 98%